A group acceptance sampling plan for ‘Another Generalized Transmuted‐Exponential Distribution’ based on truncated lifetimes - Fayomi, Aisha; Khan, Khushnoor (Quality and reliability engineering international, 2024)
The present paper focuses on the group acceptance sampling plan when the characteristic of interest follows Another Generalized Transmuted‐Exponential distribution. The probability of acceptance is calculated using mean life as a quality parameter for obtaining design parameters such as sample size ‘n’ and acceptance number ‘c’. The values of the operating characteristic function are determined for different quality levels. The plan satisfies both the producer's and consumer's risks at specified quality levels. Relevant r codes using Monte Carlo simulation are appended for use by academia and practitioners. The simulated results of the study are exhibited in the form of tables and explained with relevant examples. Results of the proposed plan are compared with the results generated using maximum likelihood estimates of Another Generalized Transmuted‐Exponential distribution. Easy to follow methodology of the current paper will open new vistas for applying the technique of group acceptance sampling plan to a variety of transmuted probability distributions. For illustration purposes, real data set is also analyzed to show the implementation of the proposed sampling plan.